STUDENTS’ PERCEPTION IN USING TASK-BASED INSTRUCTION (TBI) IN TEACHING ENGLISH AT MECHANICAL ENGINEERING STUDENTS OF UKI TORAJA - Rachel Rachel; Luspianto Bidang (Universitas Andi Djemma, 2020)
The objective of this research is to find out the students’ perception in using Task-Based Instruction in Teaching English at Mechanical Engineering Students of UKI Toraja. In analyzing the data of this research, the researcher employed quantitative method. The subjects of this research were the fifth semester students of Mechanical Engineering students of UKI Toraja. To get the respondents, the researcher used incidental sampling. The researcher took 27Students of Mechanical Engineering of UKI Toraja as respondents. The data of this research was collected by questionnaire. It was closed-ended questionnaire. The obtained data were analyzed by using Likert Scale. The questionnaire consists of 10 positive statement and 10 negative statement. The result of the research of Students’ Perception in Using Task-Based Instruction (TBI) in Teaching English at Mechanical Engineering Students of UKI Toraja were positive perception. It could be concluded by mean score of students’ perception. The mean score of students’ perception were 65.19. It was categorised into positive perception because 65.19 ≥ 60.